Swedberg's Swensk Ordabok - Språkbanken Text (University of Gothenburg, 2024)
Swedberg's Swensk Ordabok

Swedbergs Swensk Ordabok
Swedbergs Swensk ordabok
Keywords: Language Technology (Computational Linguistics); lexicon; Natural Language Processing; Språkbehandling och datorlingvistik